PROPOSAL OF THE SOCIAL CONTRACT IN MANAGEMENT AS INSTRUMENT OF ANALYSIS FOR THE EMPLOYMENT RELATION. THE EXPERIENCE OF AUTOMOTIVE INDUSTRY IN ROMANIA - Muresanu Doina (Annals of the University of Oradea: Economic Science, 2012)
The communication presents the partial results of a research proposing the social contract as a new instrument of analysis for the employment relation in a social context in change, such as the case of Rumania. Until then, the research which aimed at the employment relation which is formed between the employer and the employees widely appealed to the concept of psychological contract (Rousseau, 1989; 1995). The psychological contract, defined as the perception of the mutual obligations assumed by the employee and by the employer, benefited from a fashion effect in the 1990s, when the economic difficulties questioned the model of classic employment relation based on loyalty. However, most of the empirical works on the psychological contract are static studies, for the greater part elaborated by questionnaire, which do not allow to define the impact of the social context change on the evolution of the employment relation. Although certain studies are interested in a context of change (Dick, 2010), most of the past works describe the contents and the evaluation of the psychological contract in an unchanging social environment. Yet, we saw it in the case of the ex-communist countries or those of the Northern Africa, the change in the environment of the employment relation is more present than ever. Our communication proposes a research frame which would be more suited to the understanding of the employment relation in a society in change. To do it, we rely on the social contract in management, which we define as the ensemble of the norms and of the tacit laws existing in a society or a group given with regard to the relation of employment. The approach by the social contract presents the advantage of including multiple elements bound to a societal context, such as the laws, the national culture, the faiths shared by the business environment, etc. (Rousseau, 1995). It offers a new frame of analysis for the employment relation by suggesting that it is through the systematic and global vision of the values and standards relating to the employment relation, that we can better comprehend the consequences of a change of the employment relation. Given its exploratory character, we use an inductive, thus qualitative, methodology, to perform this research. The partial results of the analysis of the interviews led in two Romanian companies during the summer of 2010 allowed us to identify several components, which we called "terms" of the social contract. These results will deliver to the practitioners and to the researchers in management a relevant tool to better understand the relation of employment in different national cultures as well as a measuring instrument for the quality of the employee-employer relation. Our communication ends by proposing various paths of reflection which will allow to use this approach in future researches concerning the employment relation.